Molecular targets of isothiocyanates in cancer: Recent advances. Issue 8 (10th February 2014) - Gupta, Parul; Kim, Bonglee; Kim, Sung‐Hoon; Srivastava, Sanjay K.; Traber, Maret G.
<x xml:space="preserve">Abstract</x> Cancer is a multistep process resulting in uncontrolled cell division. It results from aberrant signaling pathways that lead to uninhibited cell division and growth. Various recent epidemiological studies have indicated that consumption of cruciferous vegetables, such as garden cress, broccoli, etc., reduces the risk of cancer. Isothiocyanates (ITCs) have been identified as major active constituents of cruciferous vegetables. ITCs occur in plants as glucosinolate and can readily be derived by hydrolysis. Numerous mechanistic studies have demonstrated the anticancer effects of ITCs in various cancer types. ITCs suppress tumor growth by generating reactive oxygen species or by inducing cycle arrest leading to apoptosis. Based on the exciting outcomes of preclinical studies, few ITCs have advanced to the clinical phase. Available data from preclinical as well as available clinical studies suggest ITCs to be one of the promising anticancer agents available from natural sources. This is an up‐to‐date exhaustive review on the preventive and therapeutic effects of ITCs in cancer.